Evaluation of cost-effective maintenance rations on nutrient intakeand physiological responses of unproductive Tharparkar cattle - BHUPENDER; PANDEY, HARI OM; DUTTA, NARAYAN; K S, AMBILI; I, MOTE SUJIT; SINVER, MAHENDRA; DAS, AJOY; DABAS, RAVI (The Indian Journal of Animal Sciences, 2026)
Management of unproductive cattle is economically challenging, particularly under resource-constrained conditions where feeding costs dominate the total expenditure. Therefore, development of cost-effective, nutritionally adequate maintenance rations is essential for sustainable livestock management. This study aimed to evaluate the effect of such rations on nutrient intake, physiological responses, and economic efficiency in unproductive Tharparkar cattle. A 60-day feeding trial was conducted using twenty-four non-pregnant, nonlactating Tharparkar cows randomly allocated to four dietary treatments: control (T0; conventional ration), T1 (cost-effective concentrate-based ration), T2 (total mixed ration), and T3 (urea-treated wheat straw supplemented with minimal concentrate). Dry matter intake, body weight, hematological indices, serum biochemical parameters, and stress biomarkers were measured. Dry matter intake and body weight remained statistically similar (P > 0.05) across all groups, indicating that the experimental rations met maintenance requirements. Hematological and serum biochemical parameters remained within normal physiological ranges, confirming the metabolic safety. Serum urea concentration was significantly higher (P < 0.001) in T3 (19.08 ± 0.36 mg/dL) compared to T0 (12.54 ± 0.32 mg/dL) at day 60, but remained within acceptable limits. Stress indicators, including superoxide dismutase activity and serum cortisol, were unaffected by dietary treatments. These findings demonstrated that urea treated straw and cost-effective rations provide a nutritionally adequate and economically viable strategy for maintaining unproductive cattle under resource-constrained conditions.